Pemanfaatan Air Cucian Beras dengan Campuran Jamur Trichoderma sp untuk Meningkatkan Pertumbuhan Tanaman Tomat (Solanum lycopersicum) - Dewi Novianti; Salni Salni; Ita Emilia; Dian Mutiara (Universitas PGRI Palembang, 2022)
The use of organic fertilizers anticipates the negative impact of using inorganic fertilizers on the environment. Research on the use of rice washing water mixed with Trichoderma sp fungus as organic fertilizer to increase the growth of tomato plants (Solanum lycopersicum) aims to determine the utilization of rice washing water mixed with Trichoderma sp fungus Â as organic fertilizer to increase the growth of tomato plants (Solanum lycopersicum). The study used 4 different concentrations of treatment and as a control only used sterile distilled water. Based on the results of the study that the different treatments gave different results. The control treatment gave the lowest yield on tomato plant growth which included plant height and number of leaves compared to the treatment with rice washing water mixed with Trichoderma sp. The application of rice washing water mixed with Trichoderma sp fungus was proven to increase the growth of tomato plants.